Conversion and Narrative : Reading and Religious Authority in Medieval Polemic - Szpiech, Ryan (Book collections on Project MUSE., 2013)
The author draws on medieval Christian, Jewish, and Muslim polemics to investigate the role of narrative in the representation of conversion. By investigating conversion not as individual experience but as expression of communal visions of history, he shows how the narratives dramatize the conflict of ideas in disputational writing.